Czech Republic : Selected Background Studies. (IMF Staff Country Reports; Country Report ;, 1995)
This paper examines a few selected aspects of adjustment and restructuring in the Czech enterprise sector. It examines financial performance of the Czech enterprise sector, drawing on data reported by nonfinancial enterprises to the Czech Statistical Office (CSO) in 1993. The findings reveal that significant progress has been made in the nonfinancial aspects of adjustment, but a large part of the enterprise sector has been slow to adopt measures to achieve sustainable financial viability.